2019
DOI: 10.1021/acssuschemeng.9b01284
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Photocatalysis of CH4 and CO2 into Ethylene

Abstract: Oxidative coupling of methane (OCM) using CO 2 as the oxidant is a potential advancement for methane conversion and greenhouse gases reduction. However, the reaction is usually limited by both high energy consumption and strict reaction condition. Here, we report, for the first time, photoinduced efficient ethylene (C 2 H 4 ) and CO production by OCM over TiO 2 -supported Ag nanoparticles at mild conditions. The success relies on a synergy coupling visible-light-induced strong surface plasma resonance (SPR) ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 48 publications
0
63
0
Order By: Relevance
“…9(c) shows several adsorption species generated under the irradiation due to the CO2 interaction with the photocatalyst in the region of 1300-1800 cm -1 . The bands at 1507, 1324, and 1404 cm -1 can be attributed to the adsorption of CO2 in the forms of monodentate carbonate (m-CO3 2-), bidentate carbonate (b-CO3 2-), and bicarbonate (HCO3 -), respectively [61][62][63]. The peaks displayed a slight enhancement with increasing irradiation time.…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 99%
“…9(c) shows several adsorption species generated under the irradiation due to the CO2 interaction with the photocatalyst in the region of 1300-1800 cm -1 . The bands at 1507, 1324, and 1404 cm -1 can be attributed to the adsorption of CO2 in the forms of monodentate carbonate (m-CO3 2-), bidentate carbonate (b-CO3 2-), and bicarbonate (HCO3 -), respectively [61][62][63]. The peaks displayed a slight enhancement with increasing irradiation time.…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 99%
“…Although several publications have reported photocatalytic reactions between CH 4 and CO, most are focused on reforming and do not produce any C 2 products [55] . However, Li and co‐workers reported significant ethylene yields over a 1 wt % Ag/TiO 2 catalyst at room temperature using a plasma‐assisted photocatalytic system [56] . For example, under optimized conditions, the authors observed an ethylene yield rate of about 7 μmol g −1 /h×10 2 , compared to 12 μmol g −1 /h×10 2 for CO. TPD experiments suggested that CO 2 adsorbs on TiO 2 while CH 4 adsorbs on the Ag sites.…”
Section: Co2 As An Oxidant (N2o‐ocm)mentioning
confidence: 99%
“…There have been many reports on the production of high‐value chemicals or syngas from photocatalytic CRM reactions. [ 129–132 ]…”
Section: Photocatalytic Conversion Of Methanementioning
confidence: 99%